Women labor participation in rice production in some selected areas of Thakurgaon district - Roy, Asha; Ethen, Dilshad Zahan; Tama, Riffat Ara Zannat; Begum, Ismat Ara (Research in Agriculture Livestock and Fisheries, 2015)
The present study was undertaken to analyze the participation of women labor in rice production activities covering randomly selected 50 rural households of two villages under Ranisonkail Upazila of Thakurgaon district. Data were collected from the selected households using face to face semi-structured interviews during December 2013 to February 2014. The study revealed that in rice production activities the percentage of hiring out days for women were 94.18 and 92.90 in aman and boro seasons, respectively. To determine the effects of the explanatory variables on women labor participation in rice production, Ordinary Least Square method was used. The analysis showed that age of the respondents and total household expenditure were positively related with women participation but negatively related with education, number of male earning members and farm size of the households. The study concludes that education, credit facilities, extension and motivation, need-based training should have the potential to increase womens participation in farm activities reasonably contributed to household income. Therefore, effective initiatives undertaken by the concerned agencies in improving womens education, skill acquisition training and access to information could enhance womens empowerment in order to achieve gender equality and development at all levels in the rural society of Bangladesh. Res. Agric., Livest. Fish.2(2): 239-246, August 2015